The Importance of the Maxillary and Mandibular Incisors in Predicting the Canines and Premolars Crown Widths - Mohammed Rafid A. Al-Khannaq; Mohammed Nahidh; Dunia Ahmed Al-Dulaimy (Hindawi Limited, 2022)
Background. The purpose of the present study was to use the combined mesiodistal crown widths of the mandibular and maxillary incisors as predictors for the combined mesiodistal crown widths of mandibular and maxillary canines and premolars. Materials and Methods. One hundred and twenty pairs of study models belong to 120 Iraqi adult subjects with normal dental and skeletal relations were included in the study. The crown widths of the mandibular and maxillary incisors, canines, and premolars were assessed at the maximum mesiodistal dimension on the dental casts using a digital electronic caliper with 0.01 mm sensitivity. The correlation between combined mesiodistal crown widths of the mandibular and the maxillary incisors and combined mesiodistal crown widths of mandibular and maxillary premolars and canines has been determined using Pearson's coefficient correlation test for each arch and gender. Using simple regression analysis, the equations predicting the widths of the mandibular and maxillary premolars and canines were established. The predicted and the actual mesiodistal crown width values have been compared with the use of a paired sample t-test. Results. According to the findings of the present study, males had significantly wider teeth compared to females. Correlations between the measured parameters ranged from moderate to strong. A nonsignificant difference between actual and predicted mesiodistal crown widths was discovered. Conclusions. With a high degree of accuracy, the combined mesiodistal widths of the maxillary and the mandibular incisors could be utilized for predicting the combined mesiodistal crown widths of the mandibular and maxillary canines and premolars.